ESBMC 5.0: An Industrial-Strength C Model Checker - Gadelha, Mikhail R.; Monteiro, Felipe R.; Morse, Jeremy; Cordeiro, Lucas C.; Fischer, Bernd; Nicole, Denis A. (2018 33rd IEEE/ACM International Conference on Automated Software Engineering (ASE), 2018)
ESBMC is a mature, permissively licensed open-source context-bounded model checker for the verification of single- and multithreaded C programs. It can verify both predefined safety properties (e.g., bounds check, pointer safety, overflow) and user-defined program assertions automatically. ESBMC provides C++ and Python APIs to access internal data structures, allowing inspection and extension at any stage of the verification process. We discuss improvements over previous versions of ESBMC, including the description of new front- and back-ends, IEEE floating-point support, and an improved k-induction algorithm. A demonstration is available at https://www.youtube.com/watch?v=YcJjXHlN1v8.